Mathematical writing ability in Problem Based Learning observed from the level of logical-mathematical intelligence - Virgonanto, Titis Hari; Pujiastuti, Emi; Prabowo, Ardhi (Department of Mathematics, Universitas Negeri Semarang, 2019)
The purpose of this study were to (1) prove the students' mathematical writing ability in the application of PBL achieve classical mastery criteria; (2) describe the mathematical writing ability of students in PBL observed from the level of logical-mathematical intelligence. The research used a mixed-method. The population of this study was 278 VIIth grade students in SMP 4 Kudus. The sample in this study was 32 students of VII-A class. Quantitative data sampling was done using simple random sampling technique. Quantitative data were obtained using tests. Quantitative data analysis used the normality test, homogeneity test, t-test, and z-test. The subjects in this study were 6 students. Qualitative data analysis was the analysis of data from interviews. The results showed that (1) the mathematical writing ability of VIIth grade students observed from the level of logical-mathematical intelligence achieved classical mastery criteria; (2) Students with high, moderate and low logical- mathematical intelligence levels met all three aspects of their mathematical writing ability, such as written text, drawing, and mathematical expression.